2011
DOI: 10.3897/zookeys.100.1523
|View full text |Cite
|
Sign up to set email alerts
|

Forty years of carabid beetle research in Europe – from taxonomy, biology, ecology and population studies to bioindication, habitat assessment and conservation

Abstract: ‘Carabidologists do it all’ (Niemelä 1996a) is a phrase with which most European carabidologists are familiar. Indeed, during the last half a century, professional and amateur entomologists have contributed enormously to our understanding of the basic biology of carabid beetles. The success of the field is in no small part due to regular European Carabidologists’ Meetings, which started in 1969 in Wijster, the Netherlands, with the 14th meeting again held in the Netherlands in 2009, celebrating the 40th annive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
273
0
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 318 publications
(284 citation statements)
references
References 310 publications
(394 reference statements)
7
273
0
4
Order By: Relevance
“…In effect, previous studies have showed that the microhabitat is a determinant factor for carabid beetle diversity and community composition (e.g. Betbeder et al, 2015;Koivula et al, 1999;Kotze et al, 2011;Niemelä et al, 1992;Schirmel et al, 2015). Here we found that carabid abundance and species richness were higher in spots with denser vegetation cover (plot scale).…”
Section: Effects Of Environmental Factors On Carabid Diversitysupporting
confidence: 67%
See 1 more Smart Citation
“…In effect, previous studies have showed that the microhabitat is a determinant factor for carabid beetle diversity and community composition (e.g. Betbeder et al, 2015;Koivula et al, 1999;Kotze et al, 2011;Niemelä et al, 1992;Schirmel et al, 2015). Here we found that carabid abundance and species richness were higher in spots with denser vegetation cover (plot scale).…”
Section: Effects Of Environmental Factors On Carabid Diversitysupporting
confidence: 67%
“…Negative effects of intensification are especially critical for elements of biodiversity supporting key ecosystem functions, such as carabid beetles with regards to the pest control service in agroecosystems (Kotze et al, 2011;Kromp, 1999). However, the effects of management practices may vary across different taxa and functional groups (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…We estimated ground beetle activity density and community structure using pitfall traps, the most common method of passive sampling for ground dwelling insects [20]. Three pitfall traps were established at three regularly spaced subsampling locations along the main transect of each sampled field (n = 9 traps/field/sampling).…”
Section: Weed and Ground Beetle Community Samplingmentioning
confidence: 99%
“…Additionally, they are common prey for small mammals, birds, reptiles, amphibians, and other larger arthropods and so form an important link in ecosystem food webs (Lö vei and Sunderland 1996). Given these factors, their straightforward collection, and their sensitivity to local community differences, ground beetles have been used extensively as indicator taxa (Rainio and Niemela 2003, Kotze et al 2011, Koivula 2011. Longitudinal studies of ground beetle collections will enable inferences about invertebrate diversity under varying climate and land-use regimes.…”
Section: Focal Taxamentioning
confidence: 99%